Role of Elongin BC-containing ubiquitin ligases - Okumura, Fumihiko; Nakatsukasa, Kunio; Kamura, Takumi (Frontiers in Oncology, 2012)
The Elongin complex was originally identified as a positive regulator of RNA polymerase II. The Elongin complex is composed of a transcriptionally active A subunit and two regulatory subunits B and C. The Elongin BC complex enhances transcriptional activity of Elongin A. “Classical” SOCS box-containing proteins interact with Elongin BC complex and have ubiquitin ligase activity. They also interact with scaffold protein Cullin (Cul) and RING domain protein Rbx, and thereby are members of the Cullin RING ligase (CRL) super family. Elongin BC complex acts as an adaptor protein connecting Cul and SOCS box protein. Recently, it was demonstrated that “classical” SOCS box proteins can be further classified into two groups, Cul2 and Cul5 type proteins. “Classical” SOCS box-containing protein pVHL is further classified as a Cul2 type protein. The Elongin BC complex-containing CRL family is now classified into two distinct protein assemblies, and plays an important role in regulating a variety of cellular processes such as tumorigenesis, signal transduction, cell motility and differentiation.